THE MISSIONARY WOMEN IN THE INLAND OF AUSTRALIA AND THE AUSTRALIAN INLAND MISSION AS REPRESENTED IN BETH BECKETTâS LIFE MEMOIR - Evi Eliyanah (TEFLIN, 2010)
Abstract: This article looks at the gender dimension of religious missions administered by the Presbyterian Church in the inland Australia as represented in Beth Beckettâs life memoir written in 1947-1955. It is aimed at obtaining general ideas on the involvement of women, as the wives of missionaries, Focusing on the experience of Beth Beckett, it argues that her position as a wife of a missionary is problematic: on the one hand she did transgress the traditional idea of staying-home wife by choosing to travel along with her husband, but at the same time, she was still bound by the domestic side of the job.